FINANCIAL INCLUSION AND DEEPENING IN NIGERIA: THE CONTRIBUTION OF JAIZ BANK - Yaaba Baba Nmadu; Abubakar Mika’ilu (Share: Jurnal Ekonomi dan Keuangan Islam, 2018)
The Central Bank of Nigeria in 2012, as a sign of her commitment to the 2011 Maya Declaration, developed a financial inclusion strategy for Nigeria. The aim of the strategy, amongst others, was to reduce the percentage of adult Nigerians excluded from financial services from 46.3 percent as at 2010 to 20.0 percent by 2020 with the view to enabling them to have access to financial services, engage in economic activities and contribute to the growth and development of the country. The number of Nigerians that are included in the formal sector shall then increase from 30.0 percent in 2010 to 80.0 percent by the year 2020. By this, Nigeria had committed herself to reducing the population of unbanked and under-banked adults by about 50.0 percent by the year 2020. Maya declaration recognises the criticality of inclusive financing to not only inclusive growth but also global financial stability, financial deepening and poverty reduction for about 2.5 billion unbanked adults across the globe. This study is a maiden attempt to explore the contribution of the recently established Islamic bank (Jaiz bank) in Nigeria towards the reduction of both the unbanked and under-banked adult population since its inception in 2012. The study used an exploratory approach and concludes that Jaiz bank is immensely helping the country in her quest to satisfy the Maya commitments. The study recommends, among others that special consideration is given to banks of such standings to aid rapid expansion of access to finance for Nigerians who ordinarily wouldn’t have easy access to banking facilities.=============================================================Inklusi Keuangan dan Pendalamannya di Nigeria: Kontribusi Bank Jaiz. Sebagai bagian dari komitmennya terhadap Deklarasi Maya 2011, Bank Sentral Nigeria pada tahun 2012 mengembangkan strategi inklusi keuangan untuk Nigeria. Tujuannya, antara lain, adalah untuk mengurangi persentase jumlah orang dewasa di Nigeria yang belum tersentuh jasa keuangan dari 46,3 persen pada 2010 menjadi 20,0 persen pada 2020 sehingga memungkinkan mereka memiliki akses ke layanan keuangan, berperan dalam kegiatan ekonomi dan berkontribusi pada pembangunan negara. Harapannya, jumlah orang Nigeria yang masuk dalam sektor formal akan terdongkrak dari 30,0 persen pada tahun 2010 menjadi 70,0 persen pada tahun 2020. Untuk itu, Nigeria telah berkomitmen untuk mengurangi jumlah orang yang unbanked dan under-banked sekitar 50,0 persen pada tahun 2020. Deklarasi Maya mengakui pentingnya pembiayaan inklusif yang ditujukan tidak hanya untuk pertumbuhan inklusif tetapi juga stabilitas keuangan global, pendalaman keuangan, dan pengurangan kemiskinan bagi sekitar 2,5 miliar orang yang unbankable di seluruh dunia. Penelitian ini adalah upaya perdananya untuk mengeksplorasi kontribusi bank non-bunga (Jaiz bank) yang baru didirikan di Nigeria terhadap pengurangan jumlah orang yang unbanked dan under-banked sejak didirikannya pada tahun 2012. Penelitian ini menggunakan pendekatan eksplorasi dan menyimpulkan bahwa Bank Jaiz memiliki kontribusi yang sangat besar dalam membantu Nigeria untuk memenuhi komitmennya terhadap deklarasi Maya. Kajian ini, antara lain, merekomendasikan bahwa pertimbangan khusus harus diberikan kepada bank-bank yang mempunyai peran sejenis untuk mempercepat perluasan akses keuangan bagi masyarakat Nigeria yang selama ini kesulitan dalam mengakses fasilitas perbankan.